Macro-behavior of risk in megacities : study of cities in pearl river delta region - Zhu, Tinger (2019)
Rapid urbanization in recent history results in emergence of many megacities around the world which have great vulnerability to natural disasters due to high concentration of people and assets. Therefore, hazard risk analysis and disaster loss estimation in megacities become a critical task for urban planners to assess impact of disasters, develop corresponding risk management schemes and plan for sustainable urban growth. This study focuses on two topics under macro-behavior of risk with case studies of cities in Pearl River Delta region. The first part concentrates on the exposure aspect of risk assessment and develops methodology to examine spatiotemporal dynamics of urban extent at risk from case study of flood hazard risk in Shenzhen. SLEUTH model is utilized to extrapolate urban extent in the future and urban maps are overlaid with hazard map to quantify changes in urban extents in each risk level over time. The second topic attends to loss aspect, in particular indirect loss, and explores economic interdependency among PRD cities which can be applied to estimate total loss and cascading loss from direct loss incurred by certain disaster. Input-Output modelling is adopted to establish correlations between economic sectors in all studied cities. In this study a multiregional input-output model for Shenzhen and Guangzhou is constructed based on macroeconomic data, and the analysis of the model reveals characteristics of economic link between the two cities as well as loss cascading effect. The result also discloses the significance of cascading loss in disaster loss analysis. The methodologies developed in this study can be adopted for macro-level disaster risk assessment and loss estimation for other disasters and other regions.